Un outil pour la sélection et la visualisation de flux : le package flows - Laurent Beauguitte; Timothée Giraud; Marianne Guerois (Netcom)
This note presents an R package that allows to select, analyse and visualise flows. After briefly recalling the issues and principles underlying the methods used by this tool (main flows, dominant flows and major flows), we describe the three main functions that are implemented : flows selection, indicators production about selected flows and lost information, cartography of dominant flows. Lastly, this selecting tool is applied to interurban commuters flows in the « Grand-Est » French region. This example shows the effect of choosing a variant of Nystuen and Dacey method on the resulting urban hierarchy and areas of influence.